Advances in external therapies of traditional Chinese medicine for the management of hyperuricemia: a comprehensive review - He, Minyang; Jiang, Nannan; Jiang, Lin; Tang, Tingting; Zhang, Qiyun; Xu, Qichang; Li, Songze; Zhang, Feng; Fan, Xiangcheng; Han, Jichun (Frontiers in Endocrinology, 2025)
Hyperuricemia is a prevalent metabolic disorder whose rising incidence over recent years has been closely linked to the development of gout, renal dysfunction, and cardiovascular disease, thereby exerting a substantial burden on patient quality of life. External therapies of Traditional Chinese Medicine (TCM)-including acupuncture, tuina (therapeutic massage), bloodletting, and topical herbal applications-have been practiced for centuries and encompass a diverse array of modalities. These interventions exert their therapeutic effects by modulating meridian flow, regulating qi and blood circulation, and harmonizing visceral function, which collectively promote uric acid excretion, suppress its production, and alleviate clinical manifestations of hyperuricemia. However, the heterogeneity of techniques and the complexity of underlying mechanisms pose challenges to systematic evaluation. In this review, we critically summarize current evidence on the mechanistic basis of various TCM external therapies for hyperuricemia and document their efficacy in symptom improvement. By integrating pharmacological insights and clinical outcomes, we aim to provide a comprehensive theoretical framework to guide future research and optimize the application of external TCM therapies in managing hyperuricemia.